Tricuspid regurgitation pressure gradient to diagnose pulmonary hypertension: a diagnostic accuracy study - Indah Kartika Murni; Emmanuel Mareffcita Siagian; Nurnaningsih Nurnaningsih; Nadya Arafuri (Indonesian Pediatric Society, 2022)
Background Pulmonary hypertension carries significant morbidity and mortality in children. Early diagnosis and management may improve outcomes in children with pulmonary hypertension. Heart catheterization, a gold standard for diagnosing pulmonary hypertension, is an invasive procedure and not widely available. Echocardiography can be used as an alternative diagnostic tool for pulmonary hypertension. Objective To determine the diagnostic value of tricuspid regurgitation pressure gradient on echocardiography compared to heart catheterization to diagnose pulmonary hypertension in children. Methods This diagnostic test study was done with medical record data of children with acyanotic congenital heart disease who underwent cardiac catheterization and echocardiography procedures from January 2018 to December 2020 at Dr. Sardjito Hospital, Yogyakarta, Indonesia. Data were analyzed to obtain sensitivity, specificity, positive and negative predictive values, as well as positive and negative likelihood ratios. Results A total of 98 children with acyanotic congenital heart disease were included. The sensitivity and specificity of the tricuspid regurgitation pressure gradient to determine pulmonary artery pressure compared to heart catheterization were 64.4% and 54.5%, respectively. The positive likelihood ratio was 1.42. The pre-test and post-test probability of this study were 88.7% and 91.7%, respectively. Conclusion Tricuspid regurgitation pressure gradient measured using echocardiography has poor sensitivity and specificity to diagnose pulmonary hypertension.